Major obstetric haemorrhage in Metro East, Cape Town, South Africa: a population-based cohort study using the maternal near-miss approach - Anke Heitkamp; Simcha Lot Aronson; Thomas van den Akker; Linda Vollmer; Stefan Gebhardt; Jos van Roosmalen; Johanna I. de Vries; Gerhard Theron (BMC, 2020)
Abstract Background Major obstetric haemorrhage is a leading cause of maternal mortality and accounts for one-third of maternal deaths in of Africa. This study aimed to assess the population-based incidence, causes, management and outcomes of major obstetric haemorrhage and risk factors associated with poor maternal outcome. Methods Women with major obstetric haemorrhage who met the WHO maternal near-miss criteria or died in the Metro East region, Cape Town, South Africa, were evaluated from November 2014-November 2015. Major obstetric haemorrhage was defined as haemorrhage in pregnancies of at least 20 weeks' gestation or occurring up to 42 days after birth, and leading to hysterectomy, hypovolaemic shock or blood transfusion of ≥5 units of Packed Red Blood Cells. A logistic regression model was used to analyse associations with poor outcome, defined as major obstetric haemorrhage leading to massive transfusion of ≥8 units of packed red blood cells, hysterectomy or death. Results The incidence of major obstetric haemorrhage was 3/1000 births, and the incidence of massive transfusion was 4/10.000 births in the Metro East region (32.862 births occurred during the studied time period). Leading causes of haemorrhage were placental abruption 45/119 (37.8%), complications of caesarean section 29/119 (24.4%) and uterine atony 13/119 (10.9%). Therapeutic oxytocin was administered in 98/119 (82.4%) women and hysterectomy performed in 33/119 (27.7%). The median numbers of packed red blood cells and units of Fresh Frozen Plasma transfused were 6 (interquartile range 4-7) and 3 (interquartile range 2-4), ratio 1.7:1. Caesarean section was independently associated with poor maternal outcome: adjusted OR 4.01 [95% CI 1.58, 10.14]. Conclusions Assessment of major obstetric haemorrhage using the Maternal Near Miss approach revealed that placental abruption and complications of caesarean section were the major causes of major obstetric haemorrhage. Caesarean section was associated with poor outcome.